2004
DOI: 10.1128/iai.72.6.3373-3382.2004
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Metabolite Gliotoxin Inhibits Assembly of the Human Respiratory Burst NADPH Oxidase

Abstract: Reactive oxygen species are a critical weapon in the killing of Aspergillus fumigatus by polymorphonuclear leukocytes (PMN), as demonstrated by severe aspergillosis in chronic granulomatous disease. In the present study, A. fumigatus-produced mycotoxins (fumagillin, gliotoxin [GT], and helvolic acid) are examined for their effects on the NADPH oxidase activity in human PMN. Of these mycotoxins, only GT significantly and stoichiometrically inhibits phorbol myristate acetate (PMA)-stimulated O 2 ؊ generation, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
109
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(116 citation statements)
references
References 63 publications
5
109
0
2
Order By: Relevance
“…GT is an epipolythiodioxopiperazine metabolite of pathogenic fungi which is capable of altering function and inducing apoptosis in macrophages [63]. GT has been shown to inhibit assembly of the NADPH oxidase of neutrophils via inhibition of PKC and the subsequent membrane translocation of p67 phox and p47 phox [40]. In this study we investigated the effect of GT on insect hemocytes and showed that GT inhibits both translocation of the hemocyte 67 and 47 kDa proteins and O 2 À generation upon PMA activation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…GT is an epipolythiodioxopiperazine metabolite of pathogenic fungi which is capable of altering function and inducing apoptosis in macrophages [63]. GT has been shown to inhibit assembly of the NADPH oxidase of neutrophils via inhibition of PKC and the subsequent membrane translocation of p67 phox and p47 phox [40]. In this study we investigated the effect of GT on insect hemocytes and showed that GT inhibits both translocation of the hemocyte 67 and 47 kDa proteins and O 2 À generation upon PMA activation.…”
Section: Discussionmentioning
confidence: 99%
“…This is of tremendous interest as an immunologically related protein was detected in insect hemocytes [6], possibly suggesting that this antibody recognizes a region of gp91 phox that has remained conserved, consisting of cysteine residues against which GT exerts its effect. Compared to other investigators [40], throughout this investigation low concentrations of GT were employed to inhibit membrane translocation (0.06-0.25 mg/ml compared to 1-3 mg/ml). To address this, it has been shown that gliotoxin is actively concentrated in cells in a glutathione-dependent manner and intracellular levels of the toxin can be up to 1500-fold greater than the applied concentration [64].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the toxins and enzymes it produces may facilitate its growth within the host and impair the host's immune response. In particular, toxins, such as gliotoxin and fumagillin, disrupt the formation of a functional NADPH oxidase complex in PMNs and inhibit both PMN degranulation and F-actin formation (13,14). In addition, the rodlet layer of the conidial surface silences the PMN response (15).…”
mentioning
confidence: 99%